Particle Engineering of Innovative Nanoemulsion Designs to Modify the Accumulation in Female Sex Organs by Particle Size and Surface Charge - Eike Folker Busmann; Henrike Lucas (MDPI AG, 2022)
Particle engineering of nanosized drug delivery systems (DDS) can be used as a strategic tool to influence their pharmacokinetics after intravenous (i.v.) application by the targeted adaptation of their particle properties according to the needs at their site of action. This study aimed to investigate particle properties depending on patterns in the biodistribution profile to modify the accumulation in the female sex organs using tailor-made nanoemulsion designs and thereby to either increase therapeutic efficiency for ovarian dysfunctions and diseases or to decrease the side effects caused by unintended accumulation. Through the incorporation of the anionic phospholipid phosphatidylglycerol (PG) into the stabilizing macrogol 15 hydroxystearate (MHS) layer of the nanoemulsions droplets, it was possible to produce tailor-made nanoparticles with tunable particle size between 25 to 150 nm in diameter as well as tunable surface charges between −2 to nearly −30 mV zeta potential using a phase inversion-based process. Three chosen negatively surface-charged nanoemulsions of 50, 100, and 150 nm in diameter showed very low cellular toxicities on 3T3 and NHDF fibroblasts and merely interacted with the blood cells, but instead stayed inert in the plasma. In vivo and ex vivo fluorescence imaging of adult female mice i.v. injected with the negatively surface-charged nanoemulsions revealed a high accumulation depending on their particle size in the reticuloendothelial system (RES), being found in the liver and spleen with a mean portion of the average radiant efficiency (PARE) between 42-52%, or 8-10%, respectively. With increasing particle size, an accumulation in the heart was detected with a mean PARE up to 8%. These three negatively surface-charged nanoemulsions overcame the particle size-dependent accumulation in the female sex organs and accumulated equally with a small mean PARE of 5%, suitable to reduce the side effects caused by unintended accumulation while maintaining different biodistribution profiles. In contrast, previously investigated neutral surface-charged nanoemulsions accumulated with a mean PARE up to 10%, strongly dependent on their particle sizes, which is useful to improve the therapeutic efficacy for ovarian dysfunctions and diseases.